PENGARUH DIMENSI KOMITMEN PROFESIONAL TERHADAP PERILAKU ETIS AKUNTAN PENDIDIK DI PERGURUAN TINGGI NEGERI DAN PERGURUAN TINGGI SWASTA - Bunga Asih Pratiwi (Universitas Muria Kudus, 2021)
This study aims to obtain empirical evidence the affect of the dimensions of professional commitment, namely affective professional commitment, continuance professional commitment, normative professional commitment, to ethical behavior in Accountants Educators in State Universities and Private Universities. The sample in this study was taken using a insidental sampling method. The number of sample data processed was 101. Data collection using primary data sources in the form of a questionnaire was arranged with a five-point Likerts scale. The data analysis technique of this study used multiple linear regression analysis techniques. The results showed that affective professional commitment did not influence ethical behavior. Continuance professional commitment negatively affects ethical behavior. Furthermore normative professional commitment has a positive affect on ethical behavior.